Family and school-based educational intervention on fruits and vegetable consumption of female students: Application of social cognitive theory - Maryam Hashemian; Mahdi Abdolkarimi; Mostafa Nasirzadeh (Wolters Kluwer Medknow Publications, 2022)
BACKGROUND: Fruits and vegetable (F.V) consumption is the most pivotal strategy of preventing cardiovascular diseases, obesity, diabetes, and cancers. The present study aims to evaluate the effect of educational intervention based on social cognitive theory (SCT) on consumption of F.Vs among female high schools' students in Rafsanjan (South of Iran). SUBJECTS AND METHODS: This quasi-experimental study was carried out among 272 students (intervention = 134 and control group = 138) using a multistage sampling method. The instrument used in this study included demographic characteristics, the students' F.V consumption during the past 7 days and its determinants based on the theory. Educational interventions were made in three sessions for students and two sessions for parents, teachers, and school officials. The data were analyzed by SPSS version 18 using the statistical tests of Chi-square, independent samples t-test, paired-samples t-test, and univariate model at a significant level of 0.05. RESULTS: Three months after the educational program, mean scores and standard deviation of F.V consumption and constructs in the intervention group increased significantly (P < 0.001). Respectively, 22.2% and 36.1% of the changes in the average unit of F.V consumption were the result of the present educational intervention. CONCLUSION: The intervention based on SCT with an emphasis on the interaction between student, family, and school has had an effect on F.V consumption behavior. Therefore, in forming behavior, attention is paid to the interaction of individual and interpersonal factors.